The Criticism of the “Investigation of the Literary Texts: Critical Approaches in Poetry and Narrative Texts” - Oveis Mohamadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Investigation of the Literary Texts: Critical Approaches in Poetry and Narrative Texts is a work in literary criticism in which the authors try to present a practical criticism about some selected texts, which are mostly written by contemporary Arab authors and poets. This book, as a critical criticism, does not consist of a mere description of critical theories, but the criticism is executed on the text. In this book, there are some weaknesses that are considerable and should be criticized; moreover, these weaknesses are present in lots of books and articles written in literary criticism. Then, the so-mentioned book is criticized in this article in form and content. Lack of mention of equivalences of technical terms in Latin and lack of use of footnotes or misuse of it, and also lack of coherence in the structures of narrative selected texts are the most obvious problems in the form of book. Regarding the content of book, the most important criticism is the restriction of the concept of critical theories and misreading it. In addition, the presented approaches are without a coherent structure and method and are written according to an immediate impression. Samples of these two problems are seen in dispersed ideas and incoherent analyses, simplistic readings, presentation of obvious ideas and criticisms and lack of referring to important references.